Belize : 2017 Article IV Consultation-Press Release; Staff Report; Informational Annex; Statement by the Executive Director for Belize. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights that adverse developments negatively impacted the Belizean economy in 2016, with strong expansion of tourism the only bright spot. Output is estimated to have contracted by 0.8 percent in 2016, reflecting a continued slowdown in oil production and agriculture. Fish and citrus production were hit by diseases. Growth in tourism was facilitated by improved airlift, marketing and new foreign direct investment projects. Unemployment increased to 11.1 percent in September 2016, from 10.2 percent a year earlier. Growth is projected at just under 2 percent over the medium term.